2018
DOI: 10.5792/ksrr.17.065
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Results after Anterior Cruciate Ligament Reconstruction in over 40 and under 40 Years of Age: A Meta-Analysis

Abstract: PurposeAnterior cruciate ligament (ACL) injury is one of the most common injuries that occur in the knee, and ACL reconstruction (ACLR) is commonly performed for preventing aggravation of degenerative changes and restoring of knee stability in young, athletic patients. This metaanalysis has a purpose of evaluating the clinical and arthrometrical outcomes of ACLR in a group of middle age patients (40 years and older) and comparing with patients under 40 years of age.MethodsMEDLINE, EMBASE, the Cochrane Central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Several studies have assessed the differences in clinical and functional outcomes after ACL reconstruction in older and younger adult populations. [8][9][10][11][12][13] A recent meta-analysis found no significant difference in clinical or arthrometric outcome measures after ACL reconstruction between patients older 40 years old and younger than 40 years old. 9 A systematic review by Costa et al 14 similarly found that patients older than and younger than 50 years old experience comparable improvements in patient satisfaction and knee stability, although older patients reported a reduced rate of returning to sport after surgery.…”
mentioning
confidence: 99%
“…Several studies have assessed the differences in clinical and functional outcomes after ACL reconstruction in older and younger adult populations. [8][9][10][11][12][13] A recent meta-analysis found no significant difference in clinical or arthrometric outcome measures after ACL reconstruction between patients older 40 years old and younger than 40 years old. 9 A systematic review by Costa et al 14 similarly found that patients older than and younger than 50 years old experience comparable improvements in patient satisfaction and knee stability, although older patients reported a reduced rate of returning to sport after surgery.…”
mentioning
confidence: 99%
“…37,41 Previous studies have mainly focused on patients older than 40 years, finding similar clinical outcomes between patients older than 40 years and those younger than 25 years after ACLR. 21,23 Although several studies have reported no significant difference in clinical outcomes after ACLR between patients older than 50 years and young patients, 3,17,32 few have systematically reviewed the literature to compare the benefits and adverse outcomes of ACLR between these patient groups.…”
mentioning
confidence: 99%
“…Since there are limited studies reporting the normal and 1-year recovery phase values of muscle strengths and hop performances in patients aged !25 years, it is questionable whether our results are outliers. Although several studies have reported satisfactory clinical outcomes after ACLR in older patients, 14,23 different rehabilitation strategies and time frames may be required in older patients.…”
Section: Discussionmentioning
confidence: 99%